5x-3=10x

Simple and best practice solution for 5x-3=10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=10x equation:


Simplifying
5x + -3 = 10x

Reorder the terms:
-3 + 5x = 10x

Solving
-3 + 5x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-3 + 5x + -10x = 10x + -10x

Combine like terms: 5x + -10x = -5x
-3 + -5x = 10x + -10x

Combine like terms: 10x + -10x = 0
-3 + -5x = 0

Add '3' to each side of the equation.
-3 + 3 + -5x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -5x = 0 + 3
-5x = 0 + 3

Combine like terms: 0 + 3 = 3
-5x = 3

Divide each side by '-5'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| -5k+10k+16=1+2k | | -12x-14=-74 | | 5(8+7c)=390 | | 3x+15x+7=162 | | 7a-2=10+7a+4a | | 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 | | 3(-2x+1)=7(-3x-6) | | 7(5-2a)=5(-3a+1) | | 3x-5(x-4)=-2+3x-8 | | 8-5p+4P=5+2P-9 | | 6xln(1+x)-x=0 | | -3(7x+6)=-(6x+3) | | (2x)+(4y)=154 |

Equations solver categories